2013
DOI: 10.1590/s0101-60832013000500001
|View full text |Cite
|
Sign up to set email alerts
|

Insatisfação corporal em adolescentes: uma investigação longitudinal

Abstract: Background: Evidence has shown that the prevalence of body dissatisfaction in youth has been increasing in recent years and it seems that adolescence is the main culprit. Objective: This study assessed body dissatisfaction in adolescents over one year. Methods: A total of 358 adolescents of both genders aged 11 to 14 years were investigated on three occasions (T1, T2, and T3). The investigation included collecting their height and weight for calculating body mass index (BMI) and administrating the Body Shape Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(14 citation statements)
references
References 26 publications
0
8
0
6
Order By: Relevance
“…The body weight overestimation was more common in girls, whereas the underestimation was more common in boys [2]. The high prevalence of body weight dissatisfaction among female adolescents is define in the literature as "normative discontent" [25]. During adolescence, the body weight satisfaction is very important as it affects life satisfaction and proper social interaction among peers [6,26,27].…”
Section: Dissatisfaction With Body Weight and Socio-demographic Factorsmentioning
confidence: 99%
“…The body weight overestimation was more common in girls, whereas the underestimation was more common in boys [2]. The high prevalence of body weight dissatisfaction among female adolescents is define in the literature as "normative discontent" [25]. During adolescence, the body weight satisfaction is very important as it affects life satisfaction and proper social interaction among peers [6,26,27].…”
Section: Dissatisfaction With Body Weight and Socio-demographic Factorsmentioning
confidence: 99%
“…Encontrou-se insatisfação corporal em mais de 80%, independentemente da classe social e da escolaridade materna, com maior frequência entre aquelas com sobrepeso e obesidade. Tal achado está em consonância com os da literatura, que aponta que a insatisfação corporal é a norma geral, especialmente para o sexo feminino 22,23 . Parece haver um "descontentamento normativo", que é uma generalização da insatisfação com o peso e as formas corporais, entre as mulheres 24 .…”
Section: Discussionunclassified
“…were satisfied with their weight, 15.6% wanted to gain weight, 25.3% wanted to lose < 10% and 11.1% wanted to lose ≥ 10% of their current weight.…”
Section: Objectivementioning
confidence: 99%
“…19 A longitudinal study conducted in Juiz de Fora, Minas Gerais, among 358 students aged 11 to 14 years, showed that the prevalence of body dissatisfaction increased among girls as they grew up, while the opposite was observed among boys. 25 In an evaluation on 3,096 Irish students of healthy weight, Kelly et al 26 29 or weight loss and that they regulated emotions, whereas in reality body dissatisfaction had the power to trigger the start of smoking.…”
Section: Objectivementioning
confidence: 99%